2022
DOI: 10.1021/acsomega.1c04129
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption–Desorption Behavior of Arsenate Using Single and Binary Iron-Modified Biochars: Thermodynamics and Redox Transformation

Abstract: Arsenic (As) is a dangerous contaminant in drinking water which displays cogent health risks to humans. Effective clean-up approaches must be developed. However, the knowledge of adsorption–desorption behavior of As on modified biochars is limited. In this study, the adsorption–desorption behavior of arsenate (As V ) by single iron (Fe) and binary zirconium–iron (Zr–Fe)-modified biosolid biochars (BSBC) was investigated. For this purpose, BSBC was modified using Fe-chips (FeBSBC), Fe-sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 126 publications
(242 reference statements)
0
5
0
Order By: Relevance
“…In highly P rich systems, where As( v ) to P molar ratios are lower than our current value of 1 : 29, competition effects can be more drastic. 58,59 Lack of competition effects could also be ascribed to P precipitation as Ca–P phases (such as hydroxyapatite and calcium phosphate) 60 at the high pH of BCD solutions (∼9.5–9.8) that drove P depletion from solution independently. The density of P on BCD at high Ca concentrations was higher than at low Ca concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In highly P rich systems, where As( v ) to P molar ratios are lower than our current value of 1 : 29, competition effects can be more drastic. 58,59 Lack of competition effects could also be ascribed to P precipitation as Ca–P phases (such as hydroxyapatite and calcium phosphate) 60 at the high pH of BCD solutions (∼9.5–9.8) that drove P depletion from solution independently. The density of P on BCD at high Ca concentrations was higher than at low Ca concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After four consecutive cycles, the composite still exhibited a 90% sulfamethoxazole adsorption efficiency compared with its worth for pristine adsorbent (Heo et al, 2019). Sun et al (2022) reported that the FeCl 3 -BC composite showed higher adsorption capacities for sulfamethoxazole, sulfamethazine, and sulfadiazine as 454, 400, and 294 mg g −1 , respectively, compared to the unmodified adsorbent. This could be attributed to the higher surface area of composite, H-bonding between -COOH/-OH groups in adsorbent and antibiotics molecules.…”
Section: Sorption Of Antibiotics Via Biochar-based Engineered Compositesmentioning
confidence: 99%
“…Details of various pyrolysis mechanism conditions and product yield. TABLE 2 Published reviews based on the biochar application in the removal of various types of pollutants in water(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022).…”
mentioning
confidence: 99%
“…Saccharum spontaneum Kans grass straw 13.5 Fe 3 O 4 2.0 mg g À 1 3.1 mg g À 1 Baig et al [137] 16. Rahman et al [138] ChemistrySelect maximum adsorption of 33.7 g kg À 1 for peanut straw and 27.0 g kg À 1 for rice straw biochars modified with Fe(III) at pH 5.…”
Section: Wheat Straw Biocharmentioning
confidence: 99%